Chlorophyllides: Preparation, Purification, and Application - Yi-Ting Wang; Chih-Hui Yang; Keng-Shiang Huang; Jei-Fu Shaw (Biomolecules, 2021)
Chlorophyllides can be found in photosynthetic organisms. Generally, chlorophyllides have a-, b-, c-, d-, and f-type derivatives, and all chlorophyllides have a tetrapyrrole structure with a Mg ion at the center and a fifth isocyclic pentanone. Chlorophyllide a can be synthesized from protochlorophyllide a, divinyl chlorophyllide a, or chlorophyll. In addition, chlorophyllide a can be transformed into chlorophyllide b, chlorophyllide d, or chlorophyllide f. Chlorophyllide c can be synthesized from protochlorophyllide a or divinyl protochlorophyllide a. Chlorophyllides have been extensively used in food, medicine, and pharmaceutical applications. Furthermore, chlorophyllides exhibit many biological activities, such as anti-growth, antimicrobial, antiviral, antipathogenic, and antiproliferative activity. The photosensitivity of chlorophyllides that is applied in mercury electrodes and sensors were discussed. This article is the first detailed review dedicated specifically to chlorophyllides. Thus, this review aims to describe the definition of chlorophyllides, biosynthetic routes of chlorophyllides, purification of chlorophyllides, and applications of chlorophyllides.